Why are pediatric urologists unable to predict renal deterioration using urodynamics? A focused narrative review of the shortcomings of the literature. Issue 4 (August 2022) - Weaver, J.K.; Weiss, D.A.; Aghababian, A.; Smith, A.L.; Van Batavia, J.; Long, C.J.; Tasian, G.E.; Zderic, S.A.
Summary: In this focused narrative review we set out to review the current literature addressing the utilization of UDS in patients with spina bifida (SB). We specifically analyzed 6 urodynamic parameters and their roles as predictors of upper tract deterioration in pediatric SB patients. The material available did not allow a systematic analysis or the usage of metanalysis methodology, due to the predominance of small retrospective cohorts, and high heterogeneity. We identified 10 retrospective chart reviews that met our study criteria. The results of each of these papers, as well as other studies deemed relevant to the discussion, are included in our narrative review of the literature. We summarize the current literature, offer explanations for divergences in opinion, and identify future research directions and emerging solutions with a focus on machine learning.